Class Confidence to Build a Positive Culture in Schools - Susiani, Ely Tri; Niamah, Miftakhu; Sholihah, Abdah Munfaridatus (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
Positive discipline is discipline without threats or punishment. Applying positive discipline can increase student awareness in determining the positive character of positive discipline through an agreement between the teacher and students so that students feel involved and responsible for carrying out the discipline. This study aims to determine the impact of implementing a positive culture in the formation of class beliefs at Bina Karya Medika Ponorogo Health Vocational School. One form of positive culture developed in schools is applying positive discipline. This type of research is Classroom action research. Classroom action research is carried out through a cycle consisting of four stages, starting with action planning, continuing with learning actions and observation activities, and ending with reflection to analyze the data obtained through action. The results of the study show that the application of positive discipline and becoming a class belief will make students able to work together, collaborate, and communicate with colleagues, school principals, and other school members. Habituation of the implementation of religious teachings that students believe in to create a positive culture in school/class. Give an exemplary example that starts from yourself and always uses the triangle of restitution.